PENGEMBANGAN VIDEO PEMBELAJARAN BERBANTUAN SOFTWARE BLENDER BERBASIS CONTEXTUAL TEACHING LEARNING (CTL) UNTUK MENINGKATKAN HASIL BELAJAR SISWA PADA MATERI FLUIDA STATIS PADA KELAS XI IPA 5 DI SMA NEGERI 7 MEDAN - Siregar, Bukit Tua; Hutahaean, Juniar (INPAFI (Inovasi Pembelajaran Fisika), 2025)
ABSTRACTThis research aims to (1) determine the level of validity of video media assisted by blender software based on contextual teaching learning (CTL) on the static fluid material that has been developed, (2) determine the level of practicality of video media assisted by blender software based on contextual teaching learning (CTL) learning on the material. static fluid that has been developed. (3) determine the level of effectiveness of video media assisted by blender software based on contextual teaching learning (CTL) on the static fluid material that has been developed. The results of this research are as follows (1) a valid video has been produced to be used as learning media, in terms of validation from media experts 93.87% and material experts 96.66%. (2) the level of practicality of video media from teachers is 92.5%. The student response in the small group test was 82.75%, which was included in the very practical criteria. Meanwhile in large group trials 87% with very practical criteria. (3) the level of effectiveness of the video media that has been developed is classified into the high category with an average N-gain of 0.74. Key words: development, video media, CTL, blender software, static fluid